1988
DOI: 10.1288/00005537-198809000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux as an etiologic factor in laryngeal complications of intubation

Abstract: Significant complications are encountered in some patients as a result of prolonged endotracheal intubation. The finding of low gastric pH values at postmortem examination in patients whose larynx was severely traumatized after endotracheal intubation suggested that gastroesophageal reflux (GER) is an important factor in the pathogenesis of these problems. To evaluate the occurrence and character of GER as well as its effects upon the larynx and trachea of intubated patients, clinical observations and several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(51 citation statements)
references
References 22 publications
1
49
0
1
Order By: Relevance
“…The presence of comorbidities, such as diabetes mellitus, gastroesophageal reflux, and immunosuppression, have also been shown to predispose patients to develop stenosis. 17,20,78,79 Therefore, this population would perhaps benefit from early tracheotomy. 78 The reported historical incidence of laryngotracheal stenosis after endotracheal intubation ranges from 1 to 21%, 76,80 but it is hoped that increasing knowledge about how to limit airway injury from prolonged intubation will reduce these rates.…”
Section: Larynxmentioning
confidence: 99%
“…The presence of comorbidities, such as diabetes mellitus, gastroesophageal reflux, and immunosuppression, have also been shown to predispose patients to develop stenosis. 17,20,78,79 Therefore, this population would perhaps benefit from early tracheotomy. 78 The reported historical incidence of laryngotracheal stenosis after endotracheal intubation ranges from 1 to 21%, 76,80 but it is hoped that increasing knowledge about how to limit airway injury from prolonged intubation will reduce these rates.…”
Section: Larynxmentioning
confidence: 99%
“…1,5,6 Therefore, GPR may cause voice problems in the laryngectomized patient or lead to an increase of mucositis during radiotherapy and an increased incidence of pharyngocutaneous fistula after laryngectomy.…”
mentioning
confidence: 99%
“…In the past, some experimental animal models were established to clarify the relationship between gastric acid reflux and laryngopharynx lesions [16][17][18]. Adhami et al [6] suggested that acidic refluxate, pepsin, and conjugated bile acids are the most injurious agents affecting laryngeal tissue.…”
Section: Experimental Animal Modelmentioning
confidence: 99%